2015
DOI: 10.1371/journal.pone.0141234
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Mitral Valve Degeneration Is Associated with Chromosome 15 Loci in Whippet Dogs

Abstract: Mitral valve degeneration (MVD) is the most common form of heart disease in dogs, frequently leading to left-sided congestive heart failure and cardiac mortality. Although breed-specific disease characteristics and overrepresentation point towards a genetic origin for MVD, a causative mutation and complete molecular pathogenesis are unknown. Whippet dogs are overrepresented in incidence of MVD, suggesting an inherited component in this breed. Expressivity of this condition is variable with some dogs showing ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Thus, the genetic transmission of DMVD could be revealed through precision mapping of concentrated markers in susceptible breeds. Recently, one study identified DMVD-associated loci in Whippets dogs, which is a large dog breed with a tendency to exhibit DMVD [31]. In the present study, Maltese dogs were evaluated because they are the most common breed that presents at animal hospitals in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the genetic transmission of DMVD could be revealed through precision mapping of concentrated markers in susceptible breeds. Recently, one study identified DMVD-associated loci in Whippets dogs, which is a large dog breed with a tendency to exhibit DMVD [31]. In the present study, Maltese dogs were evaluated because they are the most common breed that presents at animal hospitals in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…The disease in the dog is characterized by its ubiquity, such that all dogs will eventually develop some evidence of the disease, and there is a close relationship between age and disease severity (Han et al, 2010(Han et al, , 2013. Several pedigree breeds have a heightened susceptibility to develop the disease sooner, progress more rapidly and become more severely affected (Beardow and Buchanan, 1993;Stern et al, 2015;Lu et al, 2016). While familial valvulopathies are also found in human patients, nonsyndromic BD seems to show the closest parallels with canine MMVD as it becomes apparent between the fourth and sixth decade, but the exact prevalence in the younger adult population is unknown (Levine et al, 2015;Markby G. R. et al, 2017;Gasser et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, Stern et al tried to solve this problem by associating their results with the whippet dog breed with a continuous variable that included the age of onset of the MMVD (considered early if under 5 years of age) and a score of severity. In this study, a genome-wide significant association was identified on the region of CFA 15, containing FSTL5, and of CFA 2, containing ARHGAP26 [ 21 ].…”
Section: Introductionmentioning
confidence: 99%